2015
DOI: 10.1088/0741-3335/57/6/065003
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of transition to electron Bernstein waves from electromagnetic mode by three mode-conversion scenarios in the dipole confinement torus plasma

Abstract: Direct measurement experiments on the mode conversion to the electron Bernstein wave (EBW) have been conducted in dipole confinement torus plasmas for three excitation scenarios; i.e. perpendicular injections of an eXtraordinary mode (X-mode) from the low-and high-magnetic-field sides, and the oblique injection of an Ordinary mode (O-mode) from the low-magnetic-field side. By inserting probe antennas into plasmas, wave propagation has been directly measured. At plasma conditions for the EBW excitation, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The slow X-mode will then reach the UHR and excite the EBW. Like the O-X-B mode-conversion, the X-B mode-conversion has been welldemonstrated experimentally [32,33,34]; unlike the O-X-B mode-conversion, however, the X-B mode-conversion is difficult to study analytically, and is typically studied computationally with particle-in-cell methods [35,36,37] or full-wave solvers [38,39]. This trend can probably be attributed in large part to the inherent non-locality of the X-B mode-conversion, which will be elucidated in the following section.…”
mentioning
confidence: 99%
“…The slow X-mode will then reach the UHR and excite the EBW. Like the O-X-B mode-conversion, the X-B mode-conversion has been welldemonstrated experimentally [32,33,34]; unlike the O-X-B mode-conversion, however, the X-B mode-conversion is difficult to study analytically, and is typically studied computationally with particle-in-cell methods [35,36,37] or full-wave solvers [38,39]. This trend can probably be attributed in large part to the inherent non-locality of the X-B mode-conversion, which will be elucidated in the following section.…”
mentioning
confidence: 99%
“…As another possible heating scenario, the mode conversion to electron Bernstein wave can access to the high density region beyond the cut off density. Although the possibility has been studied in the mini-RT [6], further studies are required to explain the over dense results of the RT-1.…”
Section: High Energy Electron Core In Dipole Confinement Systemmentioning
confidence: 99%
“…The Mini-RT with a compact levitation ring magnet operated from 2003 to 2018. The recent study was focused on the excitation of electron Bernstein wave to produce a high-density plasma in low magnetic fields [6]. The ring trap 1 (RT-1) device experiments subsequently started in 2006 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Podoba et al demonstrated conversion from an O-wave to an X-wave by probe measurements of amplitude and phase of the wave field in the WEGA stellarator [11]. Uchijima et al conducted direct measurement experiments on the mode conversion to EBW in the Mini-RT by three mode-conversion scenarios, but the measured EBW wavelength is about one-order larger than the theoretical one [21].…”
Section: Introductionmentioning
confidence: 99%